Strengthening leaf physiological functioning and grain yield formation in heat-stressed wheat through potassium application - Sarwar, Muhammad; Saleem, Muhammad Farrukh; Maqsood, Hamza; Ullah, Najeeb; Khan, Aziz; Waqas, Muhammad; Sattar, Nimra; Tasneem, Muhammad; Xu, Xu; Zhangli, Hu; Shuang, Yang (Frontiers in Plant Science, 2022)
Wheat crops are highly sensitive to high temperatures during their reproductive and grain-filling phases. We hypothesized that potassium could increase thermotolerance in wheat during grain filling by protecting cellular organelles, particularly chlorophyll, from heat injury. Two wheat genotypes, Ujala-16 (relatively heat tolerant) and Anaj-17 (relatively susceptible) were grown in pots and were submitted to 4 and 8 days of heat stress under polythene sheets 1 week after anthesis. One day before the onset of heat stress, 2% potassium (K) as K2SO4 was sprayed on all the plants. Flag leaves from both genotypes were collected after 4 and 8 days of heat stress. Leaf physiology changes were measured to quantify heat damage and to understand the K-induced recovery mechanism. The crop was harvested 125 days after sowing, and grain yield data were collected. Increasing duration of heat stress significantly impaired leaf physiology and grain yield of both studied wheat genotypes. Compared with control (under optimum temperature), 4 and 8 days heat-stressed plants produced 11 and 19% lesser grain yield per spike (averaged across genotypes and in the second years of study), respectively. Likewise, 4- and 8-days heat-stressed plants had 15 and 37% (averaged across genotypes and in the second years of study) lower flag leaf photosynthesis, respectively, compared with control plants. Across the genotypes, 8-days heat caused significantly more grain yield loss in Anaj-17 during the second year than in Ujala-16. Foliar K significantly restored leaf chlorophyll, Pn, Fv/Fm by reducing cellular membrane damage in the heat-stressed plants. This physiological recovery and activation of the plant defensive system by K under high-temperature stress protected the growth and grain development. For example, K–treated plants produced 19% higher 1,000 grain weight in 8 days of heat stress (across genotypes and in the second years of study) compared with water-treated plants under the hot environment of the respective thermal regime. Our study suggests that wheat performance under terminal heat stress can be improved through the exogenous application of K.